THE EFFECT OF THE SCHOOL ENVIRONMENT ON THE ESTABLISHMENT OF STUDENT TOLERANCE - Rinduan Zain; Zahrotun Salimah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
This study analyzes the relationship and scale of influence in the school environment toward students' tolerance. This research was conducted in Senior High School State 8 Yogyakarta. The population was all 809 students. The sampling technique used in this research is probability sampling with the method stratified random sampling so that the respondents were obtained, 271 students. The independent variable was in the school environment, and the dependent variable was in the form of tolerance. The data was collected used a questionnaire. The data has been collected and analyzed using bivariate correlation analysis and simple linear regression correlation using SPSS version 16. The bivariate correlation analysis was produced a correlation coefficient of 0.43 and a significance value of 0. It showed the relationship between school environment and tolerance with enough correlation categorize so that Ha accepted and H0 rejected. Meanwhile, regression similarity Y = 37.621 + 0.525 X. The significance value of the regression test was of 0, t-count > t-table = 7.815 > 1.968. So, Ha accepted, and H0 rejected. The school environment influences students' formation tolerance in Senior High School State 8 Yogyakarta of 53%.